AIM™ platform: A new immunotherapy approach for viral diseases - Langan, David; Wang, Ruipeng; Tidwell, Keshanti; Mitiku, Selome; Farrell, Alison; Johnson, Catrina; Parks, Adam; Suarez, Lauren; Jain, Shweta; Kim, Sojung; Jones, Kristi; Oelke, Mathias; et al. (Frontiers in Medicine, 2022)
Infectious diseases are responsible for both regional and global health crises. In addition to complications of acute diseases, chronic viral infections are linked to both malignancies and autoimmune disorders. Lack of adequate treatment options for Epstein-Barr virus (EBV), Human T-lymphotropic virus type 1 (HTLV-1), and human papillomavirus (HPV) remains. The NexImmune Artificial Immune Modulation (AIM) nanoparticle platform can be used to direct T cell responses by mimicking the dendritic cell function. In one application, AIM nanoparticles can be used to enrich and expand (E+E) rare populations of multi-antigen-specific CD8+ T cells that can elicit a desired immune response. This approach, using ex vivo E+E CD8+ T cells, has demonstrated the functional relevance of targeting EBV, HTLV-1, and HPV. Our initial work was in the context of exploring T cells expanded from healthy donors and restricted to human leukocyte antigen (HLA)-A*02:01 serotype. Expanded T cells consist primarily of effector memory, central memory, and self-renewing stem-like memory T cells directed at selected viral antigen peptides presented by the AIM nanoparticle. T cells generated against either EBV- or HPV-antigens are highly polyfunctional and displayed substantial in vitro cytotoxic activity against HLA-A*02 positive target cell lines expressing the respective targeted antigens. AIM adoptive cell therapies (ACT) are also being developed for other HLA class I serotypes. The AIM nanoparticle platform is quite flexible. While this report shows the feasibility of using the AIM platform for immunotherapies to these virus-mediated diseases, there is the possibility to expand this platform for infectious diseases and cancer. Adoptive cell therapies of ex vivo E+E CD8+ autologous or allogeneic T cells specific to antigens associated with acute myeloid leukemia, multiple myeloma, and HPV are currently in the clinic. The utility and flexibility of the AIM nanoparticle platform will be expanded as we advance the second application, an AIM injectable off-the-shelf nanoparticle, which targets multiple antigen-specific T cell populations to either activate, tolerize or destroy these targeted CD8+ T cells directly in vivo, leaving non-target cells alone. In summary, the AIM injectable platform offers the potential to develop new multi-antigen specific therapies for treating infectious diseases, cancer, and autoimmune diseases.